2021
DOI: 10.3390/jpm11100998
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Patients with Late-Stage Non-Small Cell Lung Cancer in Shared Decision Making about Treatment

Abstract: Few treatment decision support interventions (DSIs) are available to engage patients diagnosed with late-stage non-small cell lung cancer (NSCLC) in treatment shared decision making (SDM). We designed a novel DSI that includes care plan cards and a companion patient preference clarification tool to assist in shared decision making. The cards answer common patient questions about treatment options (chemotherapy, chemotherapy plus immunotherapy, targeted therapy, immunotherapy, clinical trial participation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…The first reported 87% reduction in decisional conflict, 37 the other reported a mean difference of +1 indicating increased decision certainty. 43 Elsewhere, an RCT measuring disease education with and without a PtDA reported significantly reduced decisional conflict in the intervention and control groups (intervention mean(SD) difference from baseline: 8.1 (22.5), p<0.05; control mean (SD) difference from baseline: 9.1 (27.7), p<0.05), but no significant mean difference between groups (between group mean difference: 2.5, p>0.05). 39 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The first reported 87% reduction in decisional conflict, 37 the other reported a mean difference of +1 indicating increased decision certainty. 43 Elsewhere, an RCT measuring disease education with and without a PtDA reported significantly reduced decisional conflict in the intervention and control groups (intervention mean(SD) difference from baseline: 8.1 (22.5), p<0.05; control mean (SD) difference from baseline: 9.1 (27.7), p<0.05), but no significant mean difference between groups (between group mean difference: 2.5, p>0.05). 39 …”
Section: Resultsmentioning
confidence: 99%
“…A pilot controlled before and after study reported awareness of treatment options increased from 40% to 100% of participants post intervention. 43 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations